INTEGRATIVE PEDAGOGICAL APPROACHES IN DEVELOPING LEXICAL COMPETENCE - Nafisa Naimovna Xaitova (World Scientific Research Journal, 2025)
Abstract. This article analyzes the role of pedagogy in improving the lexical competencies of future teachers based on an integrative approach. The definitions of the integrative approach and its significance in the educational process are considered. Additionally, the role of pedagogy in the formation of lexical competence, the possibilities of using interactive methods, a cross-disciplinary approach, and multimedia technologies are highlighted. Conclusions are drawn about the effectiveness of applying an integrative approach in the professional training of future teachers and its importance in practice.